Pendidikan Kewargaan dan Tradisi Intelektual Mahasiswa di Perguruan Tinggi sebagai Agen Perubahan Menuju Masyarakat Madani - Khalilullah, Khalilullah (Media Akademika, 2002)
Civic education is a subject need to develop in higher education level like university. The benefit of this subject is more if it is supporterd by intellectual tradition of student. As a middle class society, students have a big potential to start making basic social changes. The successs of these changes will eventually make structure of state and society better. By this, the society will become an effective social control of the government as a basic fondation of civil society.